Longitudinal changes in bone mineral density of healthy elderly women in southern Taiwan - Chung-Hwan Chen; Lin Kang; Hsuan-Ti Huang; Je-Ken Chang; Shin-Fang Wu; Sung-Yen Lin; Yuh-Min Cheng; Herng-Chia Chiu (Elsevier, 2013)
Objective: Longitudinal data on bone decline in ethnic Chinese elderly are sparse, especially in healthy, aged women. This study reviews the longitudinal change in bone mineral density (BMD) at the femoral neck, great trochanter, and Ward's triangle in healthy elderly Taiwanese women. Materials and Methods: A prospective cohort study was conducted, with 1500 women aged ≥61 years. Fifty-four were eligible for hip evaluation and 52 underwent examination for hip BMD. Two years later, 50 women had a follow-up BMD examination. Linear regression was performed between age and bone density. The paired t test was used for BMD changes between examinations. Results: In the initial study, there was a negative relationship between BMD and age using liner regression at all three sites (p < 0.05). Two years later, there was a significant decrease in BMD at all three sites (p < 0.01). In terms of age cohorts, both age groups showed a significant decrease in BMD at the three sites studied (p < 0.01). There was a peak loss of BMD as high as 2.74% annually at the Ward's triangle in those aged 61-70 years. Conclusion: Our findings indicate that BMD is negatively correlated to aging in the healthy female. The loss of BMD at the Ward's triangle in those aged 61-70 years is faster than at other sites. Attention should be given to bone loss in ethnic Chinese females because their bone loss is more severe than that of Caucasians.